G626(P) A foundation in acute paediatrics (FAPS) – enhancing perceptions of paediatrics and stimulating speciality recruitment using a simulation recruiter course. (May 2019) - Mallett, P; Junk, C; Flannigan, C; Fitzsimons, A; Thompson, A; Bourke, T
Abstract : Background: Paediatrics, like many specialties in the UK, is experiencing a decline in applications for specialty training 1 . Reasons include perceptions of poor flexibility, arduous training programme and lack of adequate career guidance and support 2 . Transition between foundation level training and specialty training is an uncertain and stressful time 3 .In 2016, only 50% of FY2 doctors reported that they would enter directly into speciality training 4 . We believe that offering access to high-fidelity simulation course affords a unique opportunity to showcase our specialty, as encouraged by the RCPCH 2 . Methods: We designed, delivered and evaluated 'A Foundation in Acute Paediatrics Simulation' (FAPS) course aimed at offering junior doctors an introduction into the management of common paediatric conditions. A highly experienced inter-professional faculty provided an insight into a career in paediatrics and an opportunity for group discussion and tailored personal career advice. This initiative was approved by the Foundation programme director of the Northern Ireland Medical and Dental Training Agency (NIMDTA). This course was specially designed to run in the weeks prior to the opening of the national speciality application process. Results: 16 Foundation doctor candidates took part in the pilot FAPS course in November 2017. Prior to the course 11/16 (69%) candidates were unsure whether they were going to apply for paediatrics. After the course all 11 candidates indicated that that they were more likely to apply [mean score- 2.9 before vs 4.0 after; 1-very unlikely, 3-undecided, 5-Very likely to apply]. Subsequently, 15/16 candidates (94%) felt more confident in the assessment of the unwell child. This course will run annually and is now oversubscribed for the next course in November 2018. Conclusions: This was the first known use of a high-fidelity simulation recruiter course to enhance specialty recruitment within the UK. This course provides an opportunity to gain access to motivated junior trainees in a safe, simulated learning environment. It was extremely well received by the candidates, the faculty, and the regional training agency. This course actively helps in addressing the current plight of low trainee recruitment and retention in Paediatrics and could be easily replicated in other areas. References: Royal College of Paediatrics and Child Health. ST1 Paediatric Deanery/LETB Competition ratios and fill rate 2016. London, 2016. http://www.rcpch.ac.uk/ Jacob H, Shanmugalingam S and Kingdon C. Recruitment and retention in paediatrics. Arch Dis ChildDecember2016. doi:10.1136/archdischild-2016–311390 Pinnock R, Reed P, Wright M. The learning environment of paediatric trainees in New Zealand. J Paediatr Child Health2009;45:529–34 British Medical Association. The state of pre and post-graduate medical recruitment in England September 2017. https://www.bma.org.uk/collective-voice/policy-and-research/education-training-and-workforce/state-of-medical-recruitment